Deployment and test of IPv6 services in the VTHD network. - Adam, Y. (IEEE Communications magazine)
This article presents the deployment and test of IPv6 services in the very high broadband IP/WDM (VTHD) [L. Thual, 2003] network for new-generation Internet applications. The VTHD project is partially funded by the French government through the French Research Network for Telecom (RNRT). VTHD supports both IPv4 and IPv6 services, and interconnects research centers and institutions in France. It has a public autonomous system number (AS20603) and a public IPv6 subnet. It is connected to the IPv6 global network via open transit (France Telecom's international IP service for ISPs). VTHD in France compares with Internet2 in the United States. This article focuses on the implementation of the IPv6 service, IPv6 performance (in the context of a high-speed network), the advantages of given technologies, and problems encountered. The following items are developed: VTHD architecture, IPv6 address space and aggregation, transition mechanisms, routing protocols, network test performance, IPSec test performance, naming (DNS), and network management.